Social science and philosophy - Condogo, Antonia L. (Manila : Edric Publishing House, 2024)
"Social science refers to the academic disciplines concerned with the study of human society and the relationships among individuals within those societies. It uses systematic methods of empirical investigation, critical analysis, and theoretical explanation to understand ad describe social phenomena. Philosophy derives from the Greek word 'philosophia', meaning 'love of wisdom.' It is the study of fundamental questions about existence, knowledge, values, reason, mind, and language. Philosophers use critical reasoning rather than empirical methods to explore these questions."
Includes bibliography.
English.
Keywords: Social sciences; Philosophy